Development of Electronic Teaching Materials Based on Contextual Teaching and Learning (CTL) Approach to Improve High School Students' Mathematical Problem Solving Skills - Azizah, Nurul Izatul; Roza, Yenita; Kartini, Kartini (Universitas Pendidikan Mandalika, 2024)
The aim of this research is to develop approach-based electronic teaching materials Contextual Teaching And Learning (CTL) on systems of equations and linear inequalities to improve high school students' valid and practical mathematical problem solving abilities. This research method uses research and development with a 4D model. Data was collected using questionnaires, observations and interviews. The data analysis technique used is quantitative descriptive analysis. Teaching materials are said to be valid and practical if the score obtained is more than 70%. The results of this research show that electronic teaching materials are based The CTL approach was developed to increase mathematical problem solving abilities for high school students get score mean 89% with very valid category. The results of student responses in the limited trial obtained a score of 90.28% in the very practical category. The student response results in the field trial were 90.35% with very practical criteria. The teacher response results were 94.14% with the very practical category and the observation sheet 90.6% with the very practical criteria. From the results of validity and practicality, it can be seen that the teaching materials developed are suitable for use as learning resources.